Caracterización mitocondrial en fibroblastos derivados de pacientes costarricenses con CMT2B2 y ataxia ligada a PNKP - Camacho Hernández, Valeria María (2025)
Charcot-Marie-Tooth disease (CMT) represents a diverse group of inherited peripheral neuropathies. CMT2B2, an axonal form of the disease, is associated with pathogenic variants in the PNKP gene, which encodes a critical DNA repair enzyme. Since PNKP also repairs mitochondrial DNA, this study aims to investigate the effects of two pathogenic variants on mitochondria. Therefore, we analysed the expression of PNKP protein by Western blot and observed mitochondrial characteristics in fibroblasts from Costa Rican patients with CMT2B2 and ataxia. We analysed mitochondrial morphology, fusion, fission, reactive oxygen species (ROS) levels, mitochondrial mass, and membrane potential. Our findings revealed an absence of PNKP and a significant difference in mitochondrial branch length in fibroblasts from the patients analysed, suggesting a specific alteration in mitochondrial morphology. However, no significant differences were observed in mitochondrial area, perimeter, aspect ratio, membrane potential, or ROS production. These results indicate that, although there is a morphological alteration in mitochondria, the pathogenic mechanisms of CMT2B2 and ataxia in these patients may involve processes beyond the mitochondrial characteristics evaluated in this study. We consider that it may be necessary to change the study model from fibroblasts to motoneurons to gain a better understanding of the pathogenesis of these diseases or to explore other underlying mechanisms that are not related to mitochondria.